Bricks matter : the role of supply chains in building market-driven differentiation - Cecere, Lora M.; Chase, Charles W. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Corporate quality and process improvement initiatives are stalled. Satisfaction rates with current supply chain technologies have never been lower nor the failure rates as high. Yet, companies continue in the same patterns. Sharing relevant stories of success and failure from seventy-five supply chain pioneers, Bricks Matter reveals the insights of what has been learned over the course of thrity years, providing insights on the evolution of processes, and prognosticating on the future of tomorrows supply chains.
Includes bibliographical references and index.
Keywords: Business logistics